Self-Rescuers - Mukhamedov Islom Ibragimovich; Yuldashov Shukhrat Khusanboy ugli; Ashuraliev Iftikhor Gairatjon ugli (Genius Journals, 2023)
The results of the development of an insulating self-rescuer on chemically bound oxygen, which has improved weight and size characteristics, and meets the requirements of European and Russian standards, are presented.
Keywords: isolating self-rescuer; regenerative product on a matrix